2019
DOI: 10.1158/1078-0432.ccr-19-0253
|View full text |Cite
|
Sign up to set email alerts
|

A Fatty Acid Oxidation-dependent Metabolic Shift Regulates the Adaptation of BRAF-mutated Melanoma to MAPK Inhibitors

Abstract: Purpose: Treatment of BRAF V600E -mutant melanomas with MAPK inhibitors (MAPKi) results in significant tumor regression, but acquired resistance is pervasive. To understand nonmutational mechanisms underlying the adaptation to MAPKi and to identify novel vulnerabilities of melanomas treated with MAPKi, we focused on the initial response phase during treatment with MAPKi.Experimental Design: By screening proteins expressed on the cell surface of melanoma cells, we identified the fatty acid transporter CD36 as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 51 publications
9
86
1
Order By: Relevance
“…Plasticity of the melanoma cell phenotype is often driven by changes in the tumor microenvironment, such as hypoxia, pH, and nutrient supply [ 103 , 104 ]. BRAF inhibitor treatment is also associated with a change in the metabolic profile of cells, with a shift towards more mitochondrial respiration and the formation of reactive oxygen species [ 103 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plasticity of the melanoma cell phenotype is often driven by changes in the tumor microenvironment, such as hypoxia, pH, and nutrient supply [ 103 , 104 ]. BRAF inhibitor treatment is also associated with a change in the metabolic profile of cells, with a shift towards more mitochondrial respiration and the formation of reactive oxygen species [ 103 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparative analyses between melanoma cells and benign nevi show that carnitine palmitoyltransferase 2 (CPT) 2, an enzyme critical for translocation of long-chain Fas, is one of the most upregulated gene in melanoma (100). Interestingly, melanoma cells treated with MAPKi showed an increase of CD36 levels and fatty acid oxidation (FAO) levels in a manner dependent by peroxisome proliferator-activated receptor (PPAR-α) and CPT1A (101). Of note, the sustained FAO is essential for survival of BRAF V600E -mutant melanoma cells, under the MAPKiinduced metabolic stress prior to acquiring drug resistance (101).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…us, the concomitant inhibition of CPT1A, glycolysis, and MAPK synergistically inhibited tumour cell growth in vitro and in BRAF V600E -mutated melanoma mouse models [184].…”
Section: Energy Homeostasis In Resistant Braf V600e -Mutated Cancer Amentioning
confidence: 89%
“…AMPK phosphorylates and inactivates acetyl-CoA carboxylase, which impedes fatty acid synthesis and promotes lipid utilization by beta-oxidation in the mitochondria (Figure 2(d)) [183]. In fact, a recent study by Aloia has shown that upregulation of fat oxidation plays a role in the adaptive response to MAPK inhibition [184]. Particularly, the pharmacological blockade of CPT1A (the rate-limiting step for fat oxidation) reactivated glycolysis in MAPKitreated melanoma cells.…”
Section: Energy Homeostasis In Resistant Braf V600e -Mutated Cancer Amentioning
confidence: 99%